2021
DOI: 10.3390/su13105719
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Characteristics of Green Bond Markets to Facilitate Green Finance in the Post-COVID-19 World

Abstract: The COVID-19 pandemic and the global recessions have reduced the investments in green projects globally that would endanger the achievement of the climate-related goals. Therefore, the post-COVID-19 world needs to adopt the green financial system by introducing new financial instruments. In this regard, green bonds—a type of debt instrument aiming to finance sustainable infrastructure projects—are growing in popularity. While the literature does not contest their effectiveness in fighting climate change, resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(44 citation statements)
references
References 39 publications
1
40
0
3
Order By: Relevance
“…Liu et al (2017) [25] constructed a financial CGE model and found that green credit policies effectively curb investment in energy-intensive industries. In brief, the improvement of green finance can alleviate the financing constraints of enterprises in environmental protection, new energy, new materials, etc., and help provide more low-carbon products or services to support the development of environment-friendly enterprises [26]. What is more, it will reduce the capital supply to high-pollution and high-emission enterprises, forcing them to carry out technological transformation and upgrading, or reducing the scale of production to reduce carbon emissions [27].…”
Section: Green Financial Development and Carbon Emissionmentioning
confidence: 99%
“…Liu et al (2017) [25] constructed a financial CGE model and found that green credit policies effectively curb investment in energy-intensive industries. In brief, the improvement of green finance can alleviate the financing constraints of enterprises in environmental protection, new energy, new materials, etc., and help provide more low-carbon products or services to support the development of environment-friendly enterprises [26]. What is more, it will reduce the capital supply to high-pollution and high-emission enterprises, forcing them to carry out technological transformation and upgrading, or reducing the scale of production to reduce carbon emissions [27].…”
Section: Green Financial Development and Carbon Emissionmentioning
confidence: 99%
“…The existing literature on the contribution of SDGs to firm performance is limited. The objectives of SDGs are to establish sustainable, innovative strategies, and programs to help in poverty alleviation, employment opportunities, and community support while reducing environmental pollution (Chams and Garcia-Blandon 2019 ; Taghizadeh-Hesary et al 2021 ). SDGs have become a collective goal and value of business organizations, government, social organizations, and policymakers (Branco and Rodrigues 2006 ; Zeug et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the world economy along with the majority of economic sectors and entities are rooting for green finance mainly due to its prime benefit of climate change. ASEAN countries are also paying special attention to such concept, particularly in producing and employing energy resources (Taghizadeh-Hesary et al ., 2021). The opportunities for green finance in ASEAN are given in Table 1.…”
Section: Introductionmentioning
confidence: 99%